Mendicant ecclesiology and the apostolic life in the thought of the Oxford Masters, c.1250-1325 - Ebrey, AS (2023)
This thesis examines the texts and contexts in which three mendicants at the University of Oxford discussed certain ecclesiological themes in the late thirteenth and early fourteenth centuries. Although the secular-mendicant disputes at the University of Paris certainly provided a major impetus for the articulation of ideas about both the vita apostolica, as well as the structure of the contemporary Church and its orders, modern scholars have tended to impose certain artificial limitations upon their investigation into the effect of the mendicant orders’ emergence upon the development of ecclesiological thought. Firstly, they have generally limited their examination to the Parisian schools, which bore witness to the fiercest episodes of antifraternal polemic; secondly, they have tended to downplay the role that burgeoning intrafraternal tensions played in the way that ecclesiological concepts continued to be explored and refined. By examining the works of three mendicant theologians associated with the University of Oxford – the Franciscans, Thomas of York and William de la Mare, and the Dominican, Nicholas Trevet – this thesis traces the articulation of mendicant ‘aspects ecclésiologiques’ beyond the antifraternal debates at Paris. In doing so, it begins to illuminate the vitality and originality of much of the ecclesiological thought produced by mendicant theologians during this period.